Gestational periodontitis impact on the fetus and neonate - Vlad Dima; Simona Vladareanu; George Iancu; Valentin-Nicolae Varlas; Roxana Elena Bohiltea (Amaltea Medical Publishing House, 2021)
Maternal oral pathologies during pregnancy represent a controversial subject. The incidence of periodontal disease is approximatively 40% among pregnant women. Periodontal disease has been associated with several unfortunate outcomes; among them, the most important are cardiovascular disorders, respiratory infections, diabetes and Alzheimer's disease. Regarding mechanisms, bacteria enter the blood stream and cross the placenta or the inflammatory mediators can affect the fetoplacental unit or generate an increased inflammatory response with subsequent consequences on the fetus. The most disputed subjects concerning periodontal disease in pregnancy are related to the effects on the pregnancy outcome and the offspring, respectively the associations between maternal periodontal disease and small for gestational age, preeclampsia, arteriosclerosis, gestational diabetes and perinatal mortality. In order to improve neonatal outcome and ensure maternal oral health, we should assure that the necessary dental treatment is provided during the entire pregnancy, preferably between 14 and 20 gestational weeks. Moreover, women should be encouraged to received dental treatment preconceptionally.